The Sudan : contested national identities - Lesch, Ann Mosely (Indiana series in Middle East studies., 1998)
The Sudan is torn by ethnic and religious conflict, centered on the struggle over the definition of the Sudanese nation-state. Is the Sudan primarily Arab or African by culture and ethnicity? Should the political system privilege Islamic legal codes or accord equal citizenship to persons of all faiths? Ann Mosely Lesch provides a comprehensive and even-handed analysis of the unresolved struggle for a stable political system and a unified national identity.